Intercultural Integration of Immigrant Children in Border Educational Institutions (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
Interculturality has been giving a great discussion from all spheres, especially in these crucial moments of the situation in Venezuela with the immigration of schoolchildren to Colombian institutions, where it can be observed that the existing public policies in Colombia do not cover this symptomatology that is It presents in schools and especially with the practices of teachers, because it is the teachers who receive this number of children and without any experience, to mainstream interculturality within the classroom with a large number of children who arrive from Venezuelan immigration, thus seeking a form of educational improvement.
Keywords: Integration; interculturality; immigrants; border; school